DAMPAK PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP MOTIVASI BELAJAR SISWA - Adi Hardani (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study examines the impact of technology-based learning on students’ learning motivation in the digital era. The rapid development of information and communication technology has transformed the educational system from conventional to digital-based learning. Using a qualitative research method with a literature review approach, this study analyzes findings from various journals related to the application of technology in learning and its influence on student motivation. The results show that technology has a dual effect: it enhances learning engagement and flexibility but may also reduce concentration and social interaction when not properly managed. Factors influencing motivation include the use of interactive media, teacher competence, digital literacy, and learning environments. The study concludes that effective integration of technology supported by teacher guidance and adequate digital facilities can create a dynamic, enjoyable, and motivating learning atmosphere for students in Indonesia.